Eccentricity-Based Topological Invariants of Dominating David-Derived Networks. (22nd October 2021) - Imran, Muhammad; Zobair, Mian Muhammad; Shaker, Hani
Abstract : A topological index is a numerical descriptor of the molecular structure based on certain topological features of the corresponding molecular graph. Topological indices are scientific contemplations of a graph that outline its subatomic topology and are graph-invariant. In a QSAR/QSPR study, topological indices are utilized to anticipate the physico-concoction resources and bioactivity of compounds. In this paper, we study some distance-based topological indices such as eccentric connectivity index (ECI), total eccentricity index (TEI), and eccentricity-based Zagreb index for dominating David-derived networks (DD network) and provide exact formulae of the said indices. These outcomes are valuable to organize the science of hidden topologies of this network.